Diversitas Serangga Penyerbuk dan Pembentukkan Buah Tanaman Kakao (Theobroma cacao L.): Diversity of Pollinator Insects and Fruit Set of Cacao ( Theobroma cacao L.) - Nugroho, Ari; Atmowidi, Tri; Kahono, Sih (Jurnal Sumberdaya Hayati, 2019)
Cocoa (Theobroma cacao L.) is an entomophilous plant which is need insects for pollination. Pollinator insects increase cocoa’s fruit set. The aim of this research were to study diversity of pollinator insects, visiting activity of fly, Forcipomyia (Diptera), and fruit set of cocoa. Observation of pollinator insects was conducted by scan sampling method. Visiting activity of Forcipomyia were observed based on duration visit per flower, number of flowers visited per minute, and duration of activity on flowers. Pollen load on body of Forcipomyia were measured. Pollination effectiveness of insect were measured from the number and size of the cocoa fruit. Result showed that 19 species of insects visitors on cocoa flowers were observed. Nine species are pollinator of cocoa’s plants i.e. Forcipomyia, Cecidomyia, Stilobezzia, Drosophila, Orimarga, Dolichoderus, Pheidole, Megachile, and Nomia. Cocoa pollination by insects produced 3% fruit higher than flowers without insect pollination. Pollination by insects produced size and weight of fruit, and number of seed per fruit were higher than pollination without insects.